Status and dynamics of a Mute Swan population near Oxford between 1976 and 1978 - Bacon, P J (Wildfowl, 1980)
During 1976-1978 a study of the population genetics of Mute Swans Cygnus olor was carried out, concentrating on a population near Oxford. The population dynamics of swans in the Oxford study area during that period are recorded and compared to earlier findings and similar studies elsewhere in Britain. The density of non-breeders and breeding pairs is lower overall; the distribution of breeding pairs has altered, both local decreases and local increases are apparent; cygnet production per pair may be slightly higher, but the observed change in this is within expected seasonal variations. The overall production of cygnets in the area may now depend largely on a few small areas of 'good' habitat.